Epic Traditions and Resistance: Analyzing Handwritten Manuscripts of Zhetysu Folk Poets - Kabdeshova, Kuralay; Zekenova, Azhar; Uderbayev, Almas; MERUYERT, SATINBEKOVA; Mambetov, Zholdasbek (Journal of Ecohumanism, 2024)
This research paper explores the historical poems of the Zhetysu folk poets, examining how these oral traditions contribute to national liberation narratives and collective historical memory. By analyzing handwritten manuscripts passed down through generations, this study investigates the role of epic traditions in shaping identity, resistance, and the portrayal of historical events in the context of the Kazakh region of Zhetysu. The paper focuses on the intertwining of folk poetry with national liberation ideas, exploring how these poems narrate past struggles for freedom and how they continue to shape contemporary cultural and national identities. Through literary analysis, the research highlights the themes, styles, and structures within these oral epics, offering insights into the ways in which they preserve historical memory and contribute to the political and social narratives of liberation. The study also examines the methods used by these poets to embed resistance and survival into their poetry, contributing to the ongoing legacy of national consciousness.